The spitzer high-redshift radio galaxy survey - De Breuck, C.; Seymour, Nick; Stern, D.; Willner, S.; Eisenhardt, P.; Fazio, G.; Galametz, A.; Lacy, M.; Rettura, A.; Rocca-Volmerange, B.; Vernet, J. (Institute of Physics Publishing, 2010)
We present results from a comprehensive imaging survey of 70 radio galaxies at redshifts 1 < z < 5.2 using all three cameras on board the Spitzer Space Telescope. The resulting spectral energy distributions unambiguously show a stellar population in 46 sources and hot dust emission associated with the active nucleus in 59. Using a new rest-frame S3µm/S 1.6µm versus S5µm/S3µm criterion, we identify 42 sources where the rest-frame 1.6 µm emission from the stellar population can be measured. For these radio galaxies, the median stellar mass is high, 2×1011 M?, and remarkably constant within the range 1 < z < 3. At z >3, there is tentative evidence for a factor of two decrease in stellar mass. This suggests that radio galaxies have assembled the bulk of their stellar mass by z ~ 3, but confirmation by more detailed decomposition of stellar and active galactic nucleus (AGN) emission is needed. The rest-frame 500 MHz radio luminosities are only marginally correlated with stellar mass but are strongly correlated with the rest-frame 5 µm hot dust luminosity. This suggests that the radio galaxies have a large range of Eddington ratios.We also present newVery Large Array 4.86 and 8.46 GHz imaging of 14 radio galaxies and find that radio core dominance-an indicator of jet orientation-is strongly correlated with hot dust luminosity.While all of our targets were selected as narrow-lined, type 2 AGNs, this result can be understood in the context of orientation-dependent models if there is a continuous distribution of orientations from obscured type 2 to unobscured type 1 AGNs rather than a clear dichotomy. Finally, four radio galaxies have nearby (<6?) companions whose mid-IR colors are suggestive of their being AGNs. This may indicate an association between radio galaxy activity and major mergers. © 2010. The American Astronomical Society.